Microstructured optical fibres with a wide single-mode range. (March 2021) - Denisov, A N; Semjonov, S L
Abstract: We have proposed a new design of microstructured optical fibres (MOFs), containing three rings of identical circular holes around a core, with different separations between the rings. The properties of the MOFs have been analysed numerically using the finite element method (FEM), and the leakage loss in the spectral range 0.40 – 2.65 μm has been calculated for the fundamental and higher order modes at various parameters of the MOFs. We have demonstrated the presence of several local maxima in the spectral dependences of the leakage loss for higher order modes and examined the physical mechanism responsible for the formation of the maxima and the variation of their position with MOF parameters. It has been shown that the proposed MOF design allows for singlemode operation in the range 0.77 – 2.3 μm.